Willingness to pay for community-based health insurance among secondary school teachers in Katsina State, Nigeria - Ahmad Falaki, Ruqayya (2017)
Introduction: Universal health coverage is a major challenge in Nigeria where out-of-pocket payments still dominates health care financing. Out-of-pocket health financing makes it difficult for the poor and low income earners to access quality health care services. The World Health Organization views out-of-pocket spending an obstacle to health care coverage and suggested that, the only way to reduce relianceon out-of-pocket fees is for government to encourage the risk pooling payment approaches. The community based health insurance scheme was introduced in Nigeria through the National Health Insurance Scheme as an alternative means of financing health care especially for the rural poor and low income earners. The community based health insurance scheme is a stepping-stone in ensuring that all individuals have equal access to effective public health and private health care. Given the importance of such a prepayment scheme, the objective of this study is to assess the willingness of secondary schoolteachers of Katsina Local Government Area to pay for this community based insurance scheme.Methods: A cross-sectional study was conducted among 534 secondary schoolteachers from five secondary schools. Schools were selected using the cluster sampling technique. Teachers in these schools who fulfilled the inclusion criteria were recruited in the study. Data was collected from 26th July to 17th August 2016, using a self -administered questionnaire. The study used the double bounded dichotomous choice contingent valuation method to elicit the amount the secondary schoolteachers are willing to pay to enrol in the community based health insurancescheme. The respondents were asked if they are willing to pay₦2000 to enrol in the scheme. Respondents who answered yes were asked if they were willing to enrol for ₦2500, the amount was further increased to ₦3000 for those who still said yes. They are then asked what the maximum amount they are willing to pay is. Respondents who were not willing to pay up to ₦2000 to enrol were asked if they were willing to pay ₦1500, which was further decreased to ₦1000 for those who are not willing to pay that amount. Results:The response rate was 88.4%. The mean age of the respondent’s was 36.32±7.58 years. More than 62% of the respondents were males, almost half of the respondents 44.1% (n=208) have a family size of 6 to 10 family members. Mean monthly income of respondents was ₦39,192.03±₦10,900.99. The results indicated that minimum WTP amountwas ₦200 and the maximum was ₦5000. Results show age, monthly income, health status, recent illness, perceived good health status, cost of treatment, satisfaction level of quality of care, distance to health facility and awareness of health insurance to be statistically significantly associated with WTP. The predictors of willingness to pay for the community based health insurance were ages 51 to 60 years (AOR=0.207; 95%CI: 0.051-0.831; P=0.026), not having good health status (AOR=2.013; 95%CI: 0.061-0.751; P=0.016) and distance taken to health facility. That is 15mins to 30mins taken to get to a health facility (AOR=6.662; 95%CI: 3.123-14.215; P<0.001) and 15mins taken to get to a health facility (AOR=2.885; 95%CI=1.287-6.468; P=0.010). Conclusion: Our study finds that majority of the secondary school teachers of Katsina LGA of Katsina State (75.16%) were willing to enrol and pay for the community based health insurance scheme. The average amount they were willing to pay for the scheme was ₦1585 per month. Factors such as Age, Income, health status, recent illness, health status, level of care, distance to health facility and awareness off health insurance were found to be associated with willingness to pay for community based health insurance scheme. In conclusion, Community Based Health Insurance Scheme is feasible among secondary school teachers of Katsina LGA of Katsina State.